Membangkitkan Kembali Tari “Melemang” yang Tenggelam Masa - Doni Febri Hendra; Nur Sekreningsih Marsan (Institut Seni Indonesia Yogyakarta, 2020)
Reviving the Drowning Period of Melemang Dance. Melemang dance is a traditional art form. In ancient times, this dance was functioned for ceremonies in the kingdom and as a means of legalizing and celebrating the king’s existence. The performance may only be done within the palace. This dance has not been performed for a long time due to the lack of guidance from the supporting community. This research uses descriptive and analytical methods to present data objectively based on facts or phenomena as they are. Furthermore, the facts and phenomena are analyzed according to the context of the discussion. Therefore, the research objective, namely the revitalization of the Melemang dance, can be achieved.Keywords: melemang dance; drowning period; revitalization